Use of a radial artery in the treatment of patients with ischemic heart disease under cardiopulmonary bypass - Varbanets, S.; Tsvyk, A.; Pukas, A.; Rudenko, N. (Ukrainian Journal of Cardiovascular Surgery, 2018)
In this paper, the experience of UCCC in the use of the radial artery (RA) for on-pump coronary artery bypass grafting (CABG) of patients with coronary artery disease was presented. The purpose of this study was to highlight the postoperative early results and complications of RA conduit usage in the aforementioned group, also prove the safety, efficacy, feasibility of RA conduit application; on top of that, the paper presented the method of RA harvesting. Our study enrolled 42 surgical interventions with RA consuming. The average age of patients was 59.57±6.34 years (from 38 to 79 years). The age of 3 patients (7.14%) were above 70 years old. 32 (76.2%) patients experienced diabetes mellitus of II type. Chronic obstructive pulmonary disease (COPD) has been diagnosed in 32 (76.2%) patients. A body mass index >30 (23.95 to 39.06) were in 19 (45.2%) patients. The mean ejection fraction (EF) in the study group was 52.4% (30 to 64%). With respect to the comparative results, RA conduit usage demonstrated superior advantages, less complications versus vein grafts. The RA conduit utilization appears to be a viable, safe, and effective option for a durable CABG. RA can be consumed in patients for redo surgeries in the lack of saphenous veins’ grafts, in a group of patients with varicose veins of the lower extremities or obesity, diabetes mellitus and COPD.